Application of Pisicological Pressure Calculation in the Dass Scale (Depression, Anxiety, and Stress Scale) Using the Certainty Factor Method for Students of Polytechnic Nsc Surabaya - Rudianto; Achmad Fitro; Rauf Fauzan (Institute of Computer Science (IOCS), 2020)
Psychological stresses such as depression, anxiety, and stress often experienced by students can affect academic performance, physical health, and psychosocial well-being. The purpose of this research is to build a facility in the form of a website-based application for students in particular and the general public in order to know the level of psychological pressure they are experiencing. The psychological scale used is the DASS-21 (Depression, Anxiety, and Stress Scale) and the calculation uses the Certainty Factor method. In carrying out this research, there are three main stages that are carried out, namely; The first stage, looking for literature studies related to research. Second stage, conducting interviews with experts to get a certainty value on the scale that the researcher uses. Then, build an expert system using prototype development methods and web-based applications. The third stage, implementation was carried out by getting Computer Technology student respondents. This research is a new domain for the NSC Surabaya Polytechnic which will implement an expert system by utilizing the Certainty Factor method in analyzing student stress levels through intelligent applications that will be implemented in the form of a website, with the calculation of Certainty Factors, the application can produce evidence or analysis that can be used. in changing the learning system.